Phytochemical Analysis and Protein Quantitation and Profiling of Some Commercially Cultivated Mushroom Species - P., Prasad M.; Sethi, Rekha (Asian Journal of Biological and Life Sciences, 2013)
Mushroom can be defined as a macrofungus with a distinctive fruiting body. Mushrooms are recognized as natural and healthy foods and credited to be the third largest macro-fungus cultivated for food and industrial purposes worldwide. Besides containing high protein, vitamins, fibers and low calories, it also has many medicinal properties. In this study, ten samples of mushrooms were screened for phytochemicals such as Cardiac glycosides, Anthraquinones, Terpenoids, Proteins, Flavonoids, Saponins, Tannins, Lignins and Phenol. All the samples showed positive result for Terpenoids and Proteins and showed negative result for Anthraquinones, Flavonoids, Tannins, Lignins and Phenol. Most of the samples found positive for Cardiac glycosides and Saponins. Protein estimation was done by Bradford's assay and concentration found was between 0.7572 mg/ml (White Beech) to 2.5972 mg/ml (King Oyster). Crude protein extract was separated on 12% polyacrylamide gel and clear distinct band was observed with silver staining. Total bands were varied sample to sample ranging from 9 to 20 bands and different sizes from 10 kDa to 130 kDa. The described approach holds great promise for further analyses and gives support to discrimination as well as for conservation of protein resources.